Improvement of in vitro potency assays by a resting step for clinical-grade chimeric antigen receptor engineered T cells - Wang, Lei; Gong, Wenjie; Wang, Sanmei; Neuber, Brigitte; Sellner, Leopold; Schubert, Maria-Luisa; Hückelhoven-Krauss, Angela; Kunz, Alexander; Gern, Ulrike; Michels, Birgit; Hinkelbein, Mandy; Mechler, Stefanie; et al. (Cytotherapy, 2019)
Background - Chimeric antigen receptor engineered T (CAR-T) cell therapy is a promising approach currently revolutionizing the field of cancer immunotherapy. However, data concerning clinical-grade CAR-T cell stability and functionality after months of cryopreservation have not been released by companies so far. To investigate the effect of cryopreservation on CAR-T cells and to further optimize the potency assays, we performed this study. - Methods - A third generation of CD19 CAR-T cells was manufactured according to Good Manufacturing Practice (GMP) requirements, which is applied to patients in an ongoing clinical phase 1 study. Quality control tests for sterility, endotoxin and mycoplasma were performed for each batch. Stability in terms of viability, recovery, transduction efficiency and functional capacity was determined using microscopy, multiparametric flow cytometry as well as chromium-51 release tests. - Results - Up to 90days of cryopreservation had no influence on viability, recovery and transduction efficiency of CAR-T cells. However, higher cell concentration for cryopreservation could alter the cell viability and recovery but not the transduction efficiency. Moreover, directly after thawing, both the quantity and quality of the functionality of CAR-T cells were transiently hampered by the negative effects of cryopreservation. Notably, the impaired functionality could be fully restored and even strengthened after an overnight resting process. - Discussion - Cryopreservation is a challenge for the functional activity of CAR-T cells. However, CAR-T cells regain their potency by overnight incubation at 37°C, which mimics the clinical application setting. Therefore, an overnight resting step should be included in in vitro potency assays.
Gesehen am 23.09.2019